Pengaruh Model Pembelajaran RICOSRE-FC Terhadap Penalaran Ilmiah dan Self Esteem Peserta Didik Kelas X Pada Mata Pelajaran Biologi di SMA - Akbar Handoko; Wulandari Wulandari; Aryani Dwi Kesumawardani; Mazalena Mazalena; Raicha Oktafiani; Nukhbatul Bidayati Haka; Nur Hidayah (WISE Pendidikan Indonesia, 2026)
This study aims to analyze the effect of the RICOSRE-FC learning model on the scientific reasoning and self-esteem of Grade X students in Biology. This study was motivated by students’ limited ability to connect Biology concepts with everyday life phenomena, present evidence-based scientific arguments, and demonstrate confidence during the learning process. This study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The population consisted of all Grade X students at SMA Perintis 2 Bandar Lampung in the 2025/2026 academic year, while the sample consisted of class X-3 as the experimental class and class X-4 as the control class, with 32 students in each class selected through cluster random sampling. The research instruments consisted of a scientific reasoning test, a self-esteem questionnaire, observation sheets, and documentation. The data were analyzed using normality tests, homogeneity tests, N-Gain, and an independent samples t-test at a significance level of 0.05. The results showed that the experimental class achieved higher improvement than the control class, with an N-Gain score of 70.067% for scientific reasoning in the high category and an N-Gain score of 70.398% for self-esteem in the high category. The hypothesis test showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the RICOSRE-FC learning model had a significant effect on students’ scientific reasoning and self-esteem. This study concludes that RICOSRE-FC is effective in improving students’ cognitive and affective aspects through active, independent, collaborative, and reflective learning. The implication of this study indicates that RICOSRE-FC can be used as an alternative Biology learning model to strengthen scientific reasoning while building students’ confidence in 21st-century learning.